ANALISIS KESALAHAN BERBAHASA INDONESIA DALAM SKRIPSI MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING DAN PENDIDIKAN MATEMATIKA UNIVERSITAS KATOLIK WIDYA MANDALA MADIUN - Suwardo, FX; Kotikhah, Rike (Educatio Vitae, 2015)
This minithesis writing effected by researchers to seek efforts to correct the mistakes done by the students of Courses of Guidance and Counselling and Education of Mathematics in using Indonesian language properly in writing a minithesis which includes aspects of writing effective sentences, use of spelling, and word choice. This minithesis used qualitative deskripstif method. The data source in the form of minitheses, i.e. 5 minithesis students of Courses of Guidance and Counselling and 5 minithesis student of Mathematics Education. Based on the analysis of the data, in Indonesia language usage in the minithesis there are errors in the (1) writing the spelling as much as 122 errors, including 94 errors in minithesis  student  of  Course  Guidance  and  Counseling  and  28  errors  in Education of Mathematical courses, (2) the use of effective sentence as many as 10 errors in the minithesis student of Guidance and Counselling Courses and 2 errors in Education of Mathematics minithesis, and (3) the election as 6 said errors in the minithesis student of Guidance and Counselling Courses. The frequency  of  errors  that  often  arise  due  to  (1)  the  lack  of  mastery  of  the Indonesian language, (2) less meticulously mastered spelling, the use of sentence effective, and word choice, (3) factors of recurrent errors caused by incorrect understanding of the use of a good and correct spelling, and (4) factors of less care with spelling, use of effective sentences, and word choice so that mastery of language Indonesia is regarded as less important.   Key words: analysis, fault, the language of Indonesia, minithesis